La cachama blanca (Piaractus brachypomus), una especie potencial para el mejoramiento genético (2007)
ABSTRACT: In Colombia continental pisciculture has shown a significant growth (by 10% per year), because it is considered a good source of high quality protein for human beings. Some researches have proven that cachama blanca (Piaractus brachypomus) has several advantages because of its omnivorous behaviour, adaptation to different types of production, high docility, and good rate of food conversion among others. Very few studies have been done regarding white cachama`s genetic parameters such as phenotypic characterization, genetic variability, inheritance coefficient and other genetic correlation about its most important productive characteristics. This knowledge would be extremely useful at the time of making decisions concerning the establishment of programs for genetic improvement, particularly considering characteristics that impair its commercial performance in the international trade market such as the number of intramuscular spines.